Breeding soundness examination in Kedah-Kelantan bulls. - Abdullah, Megat Iskandar; Saharee, Abdul Aziz; Haron, Abdul Wahid (2010)
Breeding soundness examination (BSE) is a tool to identify and select good and potential breeder bulls. The bull is an important aspect in natural breeding in which the bull supplies semen to fertilize the cow. A study was carried out at Pusat Ternakan Haiwan Pantai Timur Kelantan using BSE as a tool to evaluate, identify and prove the claim that the Kedah-Kelantan (KK) bulls at the farm are good in their reproductive performance. The parameters evaluated in BSE included physical examination parameters of feet, legs, eyes, body score, and scrotal circumference and also internal and external examination parameters of reproductive organ. Parameters for semen evaluation which included general motility, live percentage, volume, sperm morphology and concentration, were also determined. The bulls were then classified either as satisfactory potential breeders, unsatisfactory potential breeders or differed bulls, according to the standard parameters of BSE. Ten KK bulls were selected from an active breeding herd. All of the bulls passed the minimum standards of BSE which include the bull must be free from disease and abnormality of reproductive organ, has achieved the minimal scrotal circumference size of 22.5 cm at two years of age and at least has 30% of general motility and 70% of normal sperm morphology. From the results, it is concluded that all of the bulls can be classified as satisfactory potential breeders.